Effects of varying exercise intensities on muscle strength and depressive symptoms in Chinese adolescents: A 12-week randomized controlled trial - Qing Chang; Xingrui Han; Wenlong Shen; Baoyi Yang; Zongrui Lin (PLoS ONE, 2025)
The present study investigates the effects of physical education programs with varying exercise intensities on muscle strength and depressive symptoms in adolescents, while also evaluates the role of muscle strength improvement in alleviating depressive symptoms. A total of 266 eighth-grade students were divided into three groups based on exercise intensity (low, moderate, and vigorous). Over 12 weeks, students participated in physical education sessions three times per week. Muscle strength was assessed using the standing long jump and handgrip strength tests, while depressive symptoms were measured using the Center for Epidemiologic Studies Depression Scale (CES-D). Paired t-tests and one-way ANOVA were used to evaluate intra-group and inter-group differences, respectively. Multiple linear regression analysis was conducted to examine the predictive effect of muscle strength changes on depressive symptoms. Results indicated Significant improvements in standing long jump and grip strength were observed across all groups, with the vigorous-intensity group achieving the greatest gains. Depressive symptoms improved significantly in the moderate- and vigorous-intensity groups, with the latter showing the most pronounced reductions. Notably, improvements in standing long jump significantly predicted reductions in depressive symptoms, particularly in the vigorous-intensity group, whereas handgrip strength did not. These results suggest that integrating higher-intensity physical activities into school programs may have beneficial effects on both physical and mental health. Lower-limb muscle strength improvements predict reduced depressive symptoms, underscoring the importance of targeted strength training in physical education. This clinical trial has been registered with the Chinese Clinical Trial Registry under the registration number ChiCTR2500103874.